2010
DOI: 10.1016/j.rbmo.2009.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in finger length and digit ratio (2D:4D) in ICSI children

Abstract: Intracytoplasmic sperm injection (ICSI) is used to overcome severe male-factor infertility where males are azoospermic or have poor quality spermatozoa. Perturbations of finger length (short finger length adjusted for height and high second-to-fourth digit ratio, or 2D:4D) have been described in azoospermic men and men who are rated as having low sexual attractiveness. High 2D:4D has been described in women with high fecundity. Such perturbations may be related to endocrine regulation of some homeobox genes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…Wood et al. (2003) have reported that testicular sperm retrieval in azoospermic men was more successful in men with low 2D : 4D than in men with high 2D : 4D (finger length was measured directly in this study) and, recently, Sutcliffe et al. (2010) have reported that children from intracytoplasmic sperm injection had shorter fingers and tended to have higher 2D : 4D (females only) compared with controls.…”
Section: Introductionmentioning
confidence: 51%
“…Wood et al. (2003) have reported that testicular sperm retrieval in azoospermic men was more successful in men with low 2D : 4D than in men with high 2D : 4D (finger length was measured directly in this study) and, recently, Sutcliffe et al. (2010) have reported that children from intracytoplasmic sperm injection had shorter fingers and tended to have higher 2D : 4D (females only) compared with controls.…”
Section: Introductionmentioning
confidence: 51%
“…Sutcliffe et al (2010) compared finger length relative to height in 211 children conceived by ICSI and 195 control children. They reported that the former had shorter fingers after correction for height compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Age Mean finger length -To consider finger lengths between individuals (rather than relative differences in finger length within individuals) we summed across all four fingers and obtained the mean finger length per individual (Sutcliffe et al, 2010 …”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was designed to look for transmitted fertility problems in ICSI-conceived children who may show perturbations in finger development, thus reflecting the suggested genetic link between digit length and azoospermia. 54 Digit measures were taken on 211 ICSI and 195 controls, and indeed shorter finger lengths than expected for their height were seen in both females and males conceived by ICSI. The importance of this in terms of fertility potential is not known.…”
Section: Chromosomal Defectsmentioning
confidence: 96%